In-situ prepared WSe2/Si 2D-3D vertical heterojunction for high performance self-driven photodetector. Issue 20 (15th October 2022) - Zhang, Xiwei; Shao, Jiahua; Su, Yiwen; Wang, Liang; Wang, Yibin; Wang, Xinmiao; Wu, Di
Abstract: Two-dimensional (2D) transition metal chalcogenides (TMDs) have shown tremendous feasibility as building blocks for the development of high-performance optoelectronic devices owing to their distinct electrical and optical properties. However, the relatively narrow sensing range as well as the complex fabrication technique impede their technological applications. Here, we demonstrate the mixed-dimensional van der Waals (vdW) WSe2 /Si 2D-3D vertical heterojunction by in-situ fabrication of WSe2 multilayer on pre-patterned Si, for broadband and fast-speed photodetection. Thanks to the novel high-quality vertical p-n heterojunction, the as-fabricated WSe2 /Si photodetector shows an excellent rectifying characteristic and a prominent photovoltaic effect, making the device capable of light detection in self-driven mode. Additionally, the device reveals remarkable performance in terms of a high specific detectivity of ∼8.79 × 10 13 Jones, a large responsivity of ∼294 mA/W, and a fast response time of 4.1 μs. Significantly, the device shows high sensitivity to a wide spectra (200–1550 nm) owing to the production of a type-II band structure of the WSe2 /Si vertical heterojunction. The mechanism of photo-generated carriers separation and transfer in the heterojunction is analyzed by KPFM. Our work offers a potential route to the development of unique 2D-3D heterojunction for optoelectronic devices and system applications.